Bioprospecting for fertility restoration genes in wild relatives and land races of rice from different geographic regions. Issue 1 (27th March 2017) - Dash, Amit Kumar; Samal, Rashmita; Gundimeda, Jwala Narasimha Rao; Subudhi, Hata Nath; Ravi, Nageswara Rao
Abstract: Hybrid rice development, a major advance in rice breeding, has demonstrated its immense potential in enhancing the rice productivity. In the three line system of hybrid rice, the restoration of fertility of the widely used wild-abortive type of cytoplasmic male sterility is controlled by Rf3 and Rf4, two fertility restoration genes. Exploration for restorers in diverse genetic backgrounds is a critical step in hybrid rice breeding. As genetic resources constitute the major source of new genes/alleles, an attempt was made to assess the distribution of these two restorer genes in the native populations collected from the geographic regions known to be the primary and secondary centres of origin of rice. In addition, assays were performed on the populations of Oryza rufipogon and Oryza nivara, the wild progenitors of rice. The results suggest that the Rf genes are well distributed in the wild forms at a higher frequency, more in O. rufipogon, while in cultivated forms, their frequency is low, particularly for the Rf3 gene. The genes and the alleles identified in the genetically divergent, low-performing land races and wild relatives can be successfully employed for the development of new hybrid rice cultivars.